Artificial intelligence in assessment and intervention of speech and language disorders: A literature review - Balo, Eren; Ökte, Batuhan; Selvi Balo, Semra (The European Research Journal, 2025)
Artificial intelligence (AI) is a broad term that refers to the use of computers to replicate intelligent behavior with minimal human intervention. AI is rapidly transforming various sectors, including speech and language pathology, by offering innovative solutions to enhance therapeutic practices and client outcomes. Its application in speech and language pathology spans several domains, including medical diagnosis, therapeutic planning, and rehabilitation, utilizing tools such as machine learning and deep learning to enhance data analysis and pattern recognition. The primary aim of this study is to provide resources for speech and language pathologists on the topic of artificial intelligence by presenting research findings on the assessment and intervention of speech and language disorders using AI. Accordingly, AI studies in speech and language pathology found in the literature were included. The results of these studies were summarized, and information was provided on the use of AI in assessing and treating speech and language disorders, including swallowing disorders, voice disorders, acquired language disorders, motor and speech sound disorders, cleft palate speech, and developmental language disorder. Existing literature acknowledges and supports the growing popularity of AI and AI-based algorithms in speech and language pathology. Although the current evidence remains insufficient and concerns about ethics and implementation persist, advancing technology offers promise for applying AI in this field.